Toxicology in Medical Practice- Time for revolutionary change - Amin, Md Robed; Islam, Quazi Tarikul (Bangladesh Journal of Medicine, 2018)
Abstract not available Bangladesh J Medicine Jul 2018; 29(2) : 49-50